A repressão ao agricultores sem terra do Rio Grande do Sul no inicio dos anos 1960 e após o golpe de 1964 - Bárbara De La Rosa Elia (2022)
Consolidated in Rio Grande do Sul between 1960 and 1964, the Movimento dos Agricultores Sem Terra do Rio Grande do Sul (Mestre), joined the struggle for agrarian reform, being the main organ of peasant representation in the state. In this sense, it stimulated the creation and increase of landless urban associations in the state and augured a new form of demand for a more egalitarian distribution of land, the formation of encampments. The Catholic Church even state directives, is also prone to disputes and they are marked by state patronage. In this case, the emphasis is on the administration of Governor Ildo Meneghetti, from 1963 onwards, in which from 1963 onwards, due to the intensification of pressure on the peasantry, it was marked in historiography as a rehearsal for what would come from the Civil Military Coup of 1964. With its succession, the Master was dismantled, leaving, however, a balance of accumulation of experiences and knowledge. After the Mestre's trajectory, we will investigate the nuances presented as a guide to the forms of resistance established in the rural space, in addition to landless nuances close to the Mestre. In addition, this dissertation, by putting on the pressure of the dictatorial period with the repression measured in a previous moment, intends to apprehend ruptures and its militants continuities of how the Mestre and his militants were received and played a leading role in the two historical periods.